2004
DOI: 10.4269/ajtmh.2004.70.536
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Diarrhea in Children Less Than Five Years of Age in Ifakara, Tanzania

Abstract: A total of 451 stool specimens were collected from children less than five years of age with acute diarrhea from Ifakara, Tanzania and processed to detect bacterial enteropathogens, parasites, and rotaviruses. These specimens were divided into 348 from the dry season and 103 from the rainy season. Overall, diarrheogenic Escherichia coli (35.7%) were the predominant enteropathogens, with enterotoxigenic E. coli, enteroaggregative E. coli, and enteropathogenic E. coli being the most prevalent. Moreover, enteroag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
93
12
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(141 citation statements)
references
References 21 publications
32
93
12
4
Order By: Relevance
“…pathotype of E. coli isolated was neither EPEC nor ETEC, similar to previous studies (Mandomando et al, 2007;Vargas et al, 2004), but rather DAEC. Two E. coli isolates presenting mixed characteristics (mixed EAEC/DAEC pathotypes) were detected.…”
Section: Aetiology Of Diarrhoea In Moroccosupporting
confidence: 72%
See 2 more Smart Citations
“…pathotype of E. coli isolated was neither EPEC nor ETEC, similar to previous studies (Mandomando et al, 2007;Vargas et al, 2004), but rather DAEC. Two E. coli isolates presenting mixed characteristics (mixed EAEC/DAEC pathotypes) were detected.…”
Section: Aetiology Of Diarrhoea In Moroccosupporting
confidence: 72%
“…and Campylobacter spp. The role of EAEC as a relevant cause of paediatric diarrhoea has been described worldwide (Kotloff et al, 2013;Mandomando et al, 2007;Ochoa et al 2009;Vargas et al, 2004). Interestingly, the second most frequent diarrhoeagenic …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15][16][17][18][19] High isolation rates of DEC, particularly EAEC, among diarrheic children have been reported from some developing countries. Vargas and others 20 determined the distribution of enteropathogens, including bacteria, viruses, and parasites, causing diarrhea among children 5 years of age in Ifakara, Tanzania. They reported that DEC (35.7%) were the most isolated enteropathogens with predominance of EAEC (20.6%), ETEC (9.3%), and EPEC (5.3%).…”
Section: Introductionmentioning
confidence: 99%
“…and Shigella spp. are the bacterial agents which are mostly isolated from stool samples of diarrheal patients, especially in rural areas from developing countries 6,7 . Additionally, Clostridium difficile, another bacterial diarrheal agent, is a big threat for children in both community and hospitals 8,9 .…”
Section: Introductionmentioning
confidence: 99%